aYAP modRNA reduces cardiac inflammation and hypertrophy in a murine ischemia-reperfusion model - Chen, Jinmiao; Ma, Qing; King, Justin S; Sun, Yan; Xu, Bing; Zhang, Xiaoyu; Zohrabian, Sylvia; Guo, Haipeng; Cai, Wenqing; Li, Gavin; Bruno, Ivone; Cooke, John P; et al. (Life science alliance, 2020)
Myocardial recovery from ischemia-reperfusion (IR) is shaped by the interaction of many signaling pathways and tissue repair processes, including the innate immune response. We and others previously showed that sustained expression of the transcriptional co-activator yes-associated protein (YAP) improves survival and myocardial outcome after myocardial infarction. Here, we asked whether transient YAP expression would improve myocardial outcome after IR injury. After IR, we transiently activated YAP in the myocardium with modified mRNA encoding a constitutively active form of YAP (aYAP modRNA). Histological studies 2 d after IR showed that aYAP modRNA reduced cardiomyocyte (CM) necrosis and neutrophil infiltration. 4 wk after IR, aYAP modRNA-treated mice had better heart function as well as reduced scar size and hypertrophic remodeling. In cultured neonatal and adult CMs, YAP attenuated H2O2- or LPS-induced CM necrosis. TLR signaling pathway components important for innate immune responses were suppressed by YAP/TEAD1. In summary, our findings demonstrate that aYAP modRNA treatment reduces CM necrosis, cardiac inflammation, and hypertrophic remodeling after IR stress.
Keywords: Animals; novorozená zvířata; YAP-Signaling Proteins; apoptóza; infiltrace neutrofily; Myocardial Reperfusion Injury; RNA Editing; transkripční faktory; Adaptor Proteins, Signal Transducing; Myocytes, Cardiac; Apoptosis; myokarditida; adaptorové proteiny signální transdukční; Animals, Newborn; lidé; Cardiomegaly; Mice; signální proteiny YAP; Injections, Intramuscular; Transcription Factors; messenger RNA; injekce intramuskulární; reperfuzní poškození myokardu; kultivované buňky; myši; Neutrophil Infiltration; RNA, Messenger; Cells, Cultured; myši inbrední C57BL; modely nemocí na zvířatech; editace RNA; Disease Models, Animal; kardiomegalie; Myocarditis; Cell Survival; zvířata; viabilita buněk; Mice, Inbred C57BL; Myocardium; myokard; kardiomyocyty; Humans